Caesarian Section in a Sow - Sangwan, Vandana; Kumar, Ashwani; Gupta, Nikita; Kant Mahajan, Shashi; Anand, Arun (The Indian Journal of Animal Reproduction, 2025)
A 14 months old, full term pregnant sow, weighing 148 Kgs was presented with the history of straining since previ ous night. Four fetuses were delivered prior to the presentation (one naturally and 3 with assistance), but no fetus was expelled for six hours of the delivery of the last fetus. Per vaginum delivery was not possible due to narrow and edema tous vaginal passage. Caesarian section was successfully performed from right paralumbar fossa in lateral recumbency and under general anesthesia added with local infiltration. The four fetuses removed (two from each horn) were dead. The sow recovered from general anesthesia and continued to live up to one year post surgery. However, during this one year, it did not conceive.